Lübeck ligger syd for Kassel. Omkring to breve fra Kamma Rahbek og et mindedigt af Friederike Brun - Dreyer, Kirsten (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Marie-Louise Berner: The Flower Painter on His Travels. I.L. Jensen’s Letter from Paris, 1823 On 15 March 1823, the flower painter Johan Laurentz Jensen (1800–1856) wrote a letter from Paris to his friend the sculptor H.V. Bissen. In it, he describes his journey from Copenhagen across the Netherlands to Paris, and he relates his impressions and experiences, especially during the eight months spent in that city. He describes in detail the salon and the exhibition of contemporary art at the Musée du Luxembourg that year. He also makes a number of observations about his daily life, friends and activities, and lastly states that he is on his way to Sèvres, to paint on porcelain. In addition to publishing the letter in its entirety, this article provides an account of the painter’s background, and an analysis of the experiences related and observations made in the letter. It further provides background on the salon: its format and organizational principles, its location, opening hours, visitors, contents and catalogue. Additionally, detailed commentary is provided on Jensen’s observations on the art at the salon and at the Musée du Luxembourg, as well as on Jensen’s life in the city. The article concludes with an appraisal of the importance of the journey to Jensen and his art.